Studi Bibliometrik Eksplorasi Tren Glamping 2019-2024 - Laksmi, Gratia Wirata; Dewi, Triana Rosalina; Tarigan, Emenina; Oktadiana, Hera; Ingkadijaya, Rahmat (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
Glamping is a nature-based accommodation alternative popular in various parts of the world. Glamping is developing rapidly in all parts of the world, but research on the keyword glamping has yet to be widely discussed. Researchers use bibliometric analysis methods to present visualizations and knowledge about glamping. Researchers searched for SCOPUS and SINTA indexed articles published between 2019-2024 via Publish or Perish (PoP) software application. There were 245 published documents found, and only 26 published documents successfully passed the exception selection. Researchers formulated two problem statements: